STRATEGI SUPERVISI KOLABORATIF BERBASIS LESSON STUDY DALAM MENINGKATKAN KOMPETENSI DAN KINERJA GURU SDI SDN CANGKRINGMALANG II - Ratna Makhsumah; Ceria Azizah; Khusnul Setiya Anzasari; M. Furqon Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to improve the competence and performance of teachers at SDN Cangkringmalang II. The background of this research departs from the discovery of teachers' challenges in designing learning, managing classes, implementing active methods, and evaluating learning outcomes effectively, while the supervision that runs tends to be administrative and has less impact on learning practices. This research uses a qualitative approach with data collection techniques in the form of observation, interviews, questionnaires, and documentation. The supervision model developed integrates the plan do see cycle, classroom observation, collective reflection, and continuous follow-up as a collaborative and contextual coaching framework. The results of the study show that the application of collaborative supervision based on lesson studies is able to improve teachers' pedagogic and professional competence, encourage more structured, creative, and student-centered learning practices, and strengthen a reflective culture and cooperation between teachers. In addition, this model produces an adaptive supervision follow-up mechanism so that it is able to answer the need to improve the quality of learning in a sustainable manner. Thus, a collaborative supervision strategy based on lesson study can be an effective alternative in improving teacher performance and learning quality in elementary schools, and is worthy of being used as a reference for other educational units